Proton beam therapy as a rising option in treating intrahepatic cholangiocarcinoma - Lee, Jae Woo; Lee, Sang Hyub (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Intrahepatic cholangiocarcinoma (ICC) comprises about 10–15% of primary liver cancers, and the incidence is increasing (1,2). The only curative option is surgical resection, and the resectability rate at the time of diagnosis varies from 19% to 74% (3-6). Recent study showed the recurrence rate of 71% after curative resection of ICC, and 59.8% of them had local recurrence only (7). Unresectable ICC has a poor survival which the median overall survival (OS) is around 3 months when untreated (8) and palliative chemotherapy has shown survival benefit. ABC-02 trial showed biliary tract cancer treated with gemcitabine plus cisplatin had better survival than those treated with gemcitabine only (9), and now considered as the first choice chemotherapy in the treatment of unresectable or recurred ICC.